The Influence Of Investigative Experience And Investigative Capability On The Implementation Of The BPKP Aceh Investigative Audit - Cut Fitrika Syawalina; Eva Susanti; Yusliana Yusliana (UNIVED Press, 2024)
The purpose of this research is to determine the influence of investigative audit experience and the auditor's investigative abilities simultaneously on the implementation of investigative audits at the Aceh Representative Office of the Financial and Development Supervisory Agency (BPKP). This research uses multiple linear regression analysis methods with the help of the SPSS version 25 program. The data processed is data obtained from distributing questionnaires to 30 investigative auditors. The research results show that simultaneously the investigative audit experience and the auditor's investigative abilities influence the implementation of the investigative audit. Furthermore, the results of partial hypothesis testing show that the investigative audit experience and the auditor's investigative abilities each partially influence the effectiveness of implementing investigative audit procedures in proving fraud.